Cover Feature: Cationic Zinc Hydride Catalyzed Carbon Dioxide Reduction to Formate: Deciphering Elementary Reactions, Isolation of Intermediates, and Computational Investigations (Chem. Eur. J. 26/2021). Issue 26 (22nd April 2021) - Chambenahalli, Raju; Bhargav, R. M.; McCabe, Karl N.; Andrews, Alex P.; Ritter, Florian; Okuda, Jun; Maron, Laurent; Venugopal, Ajay
Abstract : Cooperativity between cationic zinc hydrides and triphenylborane is utilized to catalyze CO2 reduction. Elementary reactions provide insights into a general mechanism for zinc hydride promoted CO2 hydrosilylation and hydroboration. The significance of the zinc‐bound ligand denticity and the Lewis acid additive role in the catalytic process is highlighted. More information can be found in the Full Paper by L. Maron, A. Venugopal, et al. (DOI: 10.1002/chem.202005392 ).